PERSONNEL MANAGEMENT EFFICIENCY ANALYSIS IN THE CONTEXT OF INTELLECTUAL PROPERTY (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Today, everyone understands that in order to develop, make a profit and keep the organization competitive, management must optimize the return on investment of any resources: material, financial, and most importantly - human. When an organization really cares about people, its overall philosophy, climate and mood necessarily reflects on the results.One of the essential indicators of a management culture is leadership style. We can talk about the general style of work, which is inherent in the management apparatus of this organization as a whole, and about the individual style, which is characteristic of individual leaders. The general management style is influenced by the prevailing style features of individual leaders. And, on the contrary, an individual style is formed on the basis of a general management style, taking into account certain working conditions and personal mental, intellectual and professional characteristics of a given leader.
Keywords: personnel, personnel management system, efficiency, improvement